Análise do ensino remoto em tempos de pandemia: uma percepção sobre conteúdos de autismo por estudantes de graduação da área da saúde - Soares, Paullyne Pinheiro (2023)
The restrictions required by social distancing due to the covid-19 pandemic generated impacts mainly within universities. Considering the present scenario, this work analyzes the type of education offered during the covid-19 pandemic and the training traits of these professionals. The research talks about the students' opinion about the content about autism and the technological resources offered by UFT during the pandemic. This is a descriptive study with a qualitative approach and quantitative analysis, aiming to clarify the guiding question: is remote emergency teaching a satisfactory solution to the social distance caused by the pandemic? The analysis is a public opinion survey, where the final database was composed of 42 reports on the topic addressed. Where Through the results achieved, it is possible to observe the importance of the theme about autism to be addressed in undergraduate courses and in health courses. However, the well-structured and elaborate videos available on the Project's platform made more students access it more effectively, taking remote teaching to fulfill its role, and consequently reiterating the forms of teaching and learning.